2019
DOI: 10.3390/jcm8081212
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Tumor Effects of Low Dose Zoledronate on Lung Cancer-Induced Spine Metastasis

Abstract: Zoledronate (Zol) is an anti-resorptive/tumoral agent used for the treatment of many cancers including spinal bone metastasis. High systemic administration of a single dose is now the standard clinical care, yet it has been associated with several side effects. Here, we aimed to evaluate the effects of lower doses Zol on lung cancer and lung cancer-induced bone metastasis cells over a longer time period. Human lung cancer (HCC827) and three bone metastases secondary to lung cancer (BML1, BML3 and BML4) cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 66 publications
(89 reference statements)
0
7
0
Order By: Relevance
“…Distant metastasis is the leading cause of mortality in people with lung cancer and is present in a high percentage of patients at the time of diagnosis ( 17 ). The skeletal system is a predilection site for distant lung cancer metastasis ( 18 ). A study has shown that the incidence of LCBM is about 10–15%, while the incidence of bone metastasis in advanced lung cancer is as high as 30–40% ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Distant metastasis is the leading cause of mortality in people with lung cancer and is present in a high percentage of patients at the time of diagnosis ( 17 ). The skeletal system is a predilection site for distant lung cancer metastasis ( 18 ). A study has shown that the incidence of LCBM is about 10–15%, while the incidence of bone metastasis in advanced lung cancer is as high as 30–40% ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the United States in 2018, it was reported that lung cancer is accountable for 234,030 new cases and 154,050 deaths. Tobacco smoking is one of the most widely recognized risk factor contributing to lung cancer [109]. Lung cancer can be classified into two types, (1) non-small cell lung cancer (NSCLC), which tends to respond poorly to chemotherapy and radiation therapy; and (2) small cell lung cancer (SCLC)-this group is not common and is categorized by high proliferation rate and also sensitivity to combined chemotherapy and radiation therapy in limited-stage carcinoma cases [109].…”
Section: Lung Cancermentioning
confidence: 99%
“…We have created a dedicated section for bone metastasis and tumour dormancy. Across these organs, metastasis to the skeletal system is found to occur commonly (181)(182)(183)(184)(185). After initial tumour growth in the organ of origin, tumours cells undergo changes in cell signalling and cell-cell interactions such as reduced intercellular adhesion (186,187).…”
Section: Tissue-specific Vascular Niches and Vascular Changesmentioning
confidence: 99%